338 Biceps Metastasis Presenting as A Presumed Abscess in Patient with An Undiagnosed Non-Small Cell Lung Cancer - An Unusual Presentation. (4th May 2021) - Shah, K; Hagiga, A; Saleem, O; Elfishawi, M; Bashir, T
Abstract: Lung cancer is the most common cancer worldwide and has highest cancer mortality. Around 50% of cases present with metastasis, however skeletal muscle metastasis is rarely reported. In this case we describe a fifty-nine-year-old male patient who presented complaining of fever and a mass on the distal biceps and proximal forearm over a five-month period, with no reported improvement despite debridement and antibiotics spanning three presentations to the emergency department. Subsequent biopsy at various anatomical sites showed adenocarcinoma, later identified as metastatic from a primary non squamous-cell lung cancer (NSCLC). Metastases from lung cancer are more commonly limited to liver and adrenal glands. Presentation of such a mass in skeletal muscle would raise suspicion for the more-commonly seen soft-tissue sarcoma or hemangiomas. This case illustrates a rare example of lung cancer metastatic to skeletal muscle, more specifically, the biceps. Presentation of the mass was also unique in its morphology of an abscess with purulent discharge, raising the importance of cytology and suspicion for malignancy in an abscess unresponsive to antibiotics. Non-small cell lung cancer can present with skeletal metastasis. A work-up of a mass or abscess of the muscle should include the possibility of soft tissue metastasis.